Using the crowd as an innovation partner - Boudreau, Kevin J. (2013)
Offers guidance on choosing the best form of crowdsourcing for a given situation. Reviews how technology is helping managers address these concerns. Identifies the four ways in which organizations can tap into crowd-powered problem solving: contests, collaboration communities, complementors and labour markets. Describes the types of challenges each approach handles best and discusses how an organisation can smoothly integrate each one into its operation.